2015
DOI: 10.1139/cjpp-2014-0459
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin on acute gentamicin-induced nephrotoxicity in rats

Abstract: Our data clearly demonstrate that curcumin protects kidney from gentamicin-induced AKI via the amelioration of oxidative stress and apoptosis of renal tubular cells, thus providing hope for the amelioration of gentamicin-induced nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 38 publications
(29 reference statements)
3
50
0
Order By: Relevance
“…It has also revealed that high glucose obviously decreased SIRT1 mRNA and protein expression in rat mesangial cells [18]. Other studies have reported that SIRT1 expression was decreased in rats with gentamicin or cisplatin-induced nephrotoxicity [19,20]. Moreover, reduced SIRT1 expression has been found in mouse cortical collecting duct cells [14], in human kidney proximal tubule epithelial cells [21], and in rats with AKI induced by severe burns [22] and renal ischaemia-reperfusion injury [23].…”
Section: Discussionmentioning
confidence: 99%
“…It has also revealed that high glucose obviously decreased SIRT1 mRNA and protein expression in rat mesangial cells [18]. Other studies have reported that SIRT1 expression was decreased in rats with gentamicin or cisplatin-induced nephrotoxicity [19,20]. Moreover, reduced SIRT1 expression has been found in mouse cortical collecting duct cells [14], in human kidney proximal tubule epithelial cells [21], and in rats with AKI induced by severe burns [22] and renal ischaemia-reperfusion injury [23].…”
Section: Discussionmentioning
confidence: 99%
“…12 In this study, significant increases in serum urea and creatinine levels after exposure to cisplatin were accepted as an indicator of nephrotoxicity. A marked improvement was detected in renal histopathology and function parameters supporting the protective effect of curcumin against oxidative stress, inflammation, and tubular cell death caused by cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Curcumin, a major component of turmeric, is known to have anti-inflammatory and antioxidant effects in various pathologies. [11][12][13][14][15][16][17] In addition, recent studies have revealed that the antiapoptotic properties of curcumin against different agent-mediated acute renal injury. 11,12,15 It has been reported that curcumin prevents and ameliorates the severity of cisplatin nephrotoxicity, by inhibiting various cytokines and chemokines such as TNF-a and IL-1b and scavenging free radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysates of cultured cells were prepared as previously described [37] . After centrifugation, the protein level was determined in supernatants using a Micro BCA protein assay kit with BSA as a standard (Pierce, Thermo).…”
Section: Western Blottingmentioning
confidence: 99%